2017
DOI: 10.11594/jtls.07.03.15
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Interleukin-10, Superoxide Dismutase (SOD), and Malondialdehyde (MDA) Levels with HbA1c in Pediatric Type 1 Diabetes Mellitus

Abstract: Type 1 diabetes mellitus (T1DM) is an autoimmune disease characterized by pancreatic β-cell destruction and considered to be correlated with oxidative stress. This study aimed to investigate the association of oxidative stress [superoxide dismutase (SOD) and malondialdehyde (MDA) levels], inflammation [interleukin 10 (IL-10)], and glycemic control (HbA1c) in pediatric T1DM patients. This study included 25 T1DM subjects and 25 healthy control subjects and was designed as a cross-sectional study. SOD, MDA, and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…showed that IL-10 was negatively associated with HbA1c in type 1 diabetic patients. 47 Finally, we reported that the duration of diabetes might act as an independent predictor of PWV, with higher PWV values in those with a longer course of diabetes. Likewise, other authors found the duration of T1DM to be the strongest determinant for arterial stiffness, as measured by PWV.…”
Section: Discussionmentioning
confidence: 78%
“…showed that IL-10 was negatively associated with HbA1c in type 1 diabetic patients. 47 Finally, we reported that the duration of diabetes might act as an independent predictor of PWV, with higher PWV values in those with a longer course of diabetes. Likewise, other authors found the duration of T1DM to be the strongest determinant for arterial stiffness, as measured by PWV.…”
Section: Discussionmentioning
confidence: 78%
“…Another study has also shown that an increase in SOD may suppress the process of melanogenesis through the Tyrosinase pathway [34]. The previous studies have shown that the cytokines IL-10, IF-γ, and TNF -with their cell receptors will phosphorylate NADPH in a program that results in activation of the transcription factor NF-κB pathway through the mediation of phosphoinositide-3-kinase, MAPK, ERK1/2 [16], [34], [35]. Activated NF-κB will migrate into the nucleus and initiate the translation and transcription of various antioxidant gene expressions, including SOD [8].…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that SOD is one of the key factors reducing melanin production caused by UV irradiation [8], [10], [30]. Another study has also shown that an increase in SOD may suppress the process of melanogenesis through the Tyrosinase pathway [34]. The previous studies have shown that the cytokines IL-10, IF-γ, and TNF -with their cell receptors will phosphorylate NADPH in a program that results in activation of the transcription factor NF-κB pathway through the mediation of phosphoinositide-3-kinase, MAPK, ERK1/2 [16], [34], [35].…”
Section: Discussionmentioning
confidence: 98%
“…(24,25) The cytokines IL-10, IF-γ and TGF-β with their cell receptors will program the phosphorylate NADPH which results in the activation of the transcription factor NF-κB pathway through to the mediation of phosphoinositide-3-kinase, MAPK, ERK1/2. (26) Activated NF-κB will migrate into the nucleus, initiate the translation and transcription from various antioxidant gene expressions, including TNF-α and IL-18.…”
Section: Discussionmentioning
confidence: 99%